2021
DOI: 10.1177/1759720x211003803
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of anterior uveitis flares in patients with axial spondyloarthritis on certolizumab pegol treatment: final 2-year results from the multicenter phase IV C-VIEW study

Abstract: Introduction: Acute anterior uveitis (AAU), affecting up to 40% of patients with axial spondyloarthritis (axSpA), risks permanent visual deficits if not adequately treated. We report 2-year results from C-VIEW, the first study to prospectively investigate certolizumab pegol (CZP) on AAU in patients with active axSpA at high risk of recurrent AAU. Patients and methods: C-VIEW (NCT03020992) was a 104-week (96 weeks plus 8-week safety follow-up), open-label, multicenter study. Eligible patients had active axSpA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
(121 reference statements)
3
17
0
1
Order By: Relevance
“…Baseline characteristics for patients included in the phase 3/4 clinical studies are provided in Table 2. These studies confirmed the safety and efficacy profile of CZP in both r-axSpA and nr-axSpA populations; data pertaining to the treatment of axial symptoms in axSpA are reported in the original publications [21][22][23][24][25][26][27].…”
Section: Study Populationssupporting
confidence: 67%
See 4 more Smart Citations
“…Baseline characteristics for patients included in the phase 3/4 clinical studies are provided in Table 2. These studies confirmed the safety and efficacy profile of CZP in both r-axSpA and nr-axSpA populations; data pertaining to the treatment of axial symptoms in axSpA are reported in the original publications [21][22][23][24][25][26][27].…”
Section: Study Populationssupporting
confidence: 67%
“…Across all studies, CZP led to a reduction in the number of patients reporting AAU flares compared with placebo or the pretreatment period [27]. Data pertaining to AAU flare event rate have also been reported [24,25]. In C-VIEW, the adjusted event rate was 1.87 in the pretreatment period compared with 0.34 in the 96-week treatment period (Fig.…”
Section: Aau Flare Incidence and Event Rate And Durationmentioning
confidence: 89%
See 3 more Smart Citations